Green synthesis of zinc oxide nanoparticles using Moringa oleifera l. water extract and its photocatalytic evaluation. Issue 1 (January 2021) - Adam, F; Himawan, A; Aswad, M; Ilyas, S; Heryanto,; Anugrah, M A; Tahir, D
Abstract: Green synthesis of Zinc Oxide Nanoparticles (ZnO-NPs) using Moringa oleifera L extract is successfully carried out. ZnO-NPs is precipitated out with the help of Moringa oleifera L water extract and thermally treated at 300, 350, 400, 450, and 500°C prior characterization. The prepared ZnO-NPs were characterized using Fourier Transform Infrared (FTIR), X-ray diffraction (XRD), and The Ultraviolet-visible (UV-Vis). The photocatalytic activity was determined based on its ability to decompose methylene blue in solution. FTIR analysis result shows the absorption band at 422-497 cm −1 which associated with stretching of Zn-O, and the intensity of O-H bond (3417 cm −1 ) decreases with increasing calcination temperature. The XRD spectrum shows a significant increase in electron properties and bond formation as the temperature increase. Calcination at 500°C results in the achievement of methylene blue degradation as a pollutant model of 80% after 60 minutes of exposure. This study shows that Moringa oleifera L. water extract can be used as a green alternative in ZnO-NPs synthesis and calcination temperature affects the photocatalytic activity of the prepared nanoparticles.